Social complexity as a driving force of gut microbiota exchange among conspecific hosts in non-human primates - Pinacho-Guendulain, Braulio; Montiel-Castro, Augusto Jacobo; Ramos-Fernández, Gabriel; Pacheco-López, Gustavo (Frontiers in Integrative Neuroscience, 2022)
The emergent concept of the social microbiome implies a view of a highly connected biological world, in which microbial interchange across organisms may be influenced by social and ecological connections occurring at different levels of biological organization. We explore this idea reviewing evidence of whether increasing social complexity in primate societies is associated with both higher diversity and greater similarity in the composition of the gut microbiota. By proposing a series of predictions regarding such relationship, we evaluate the existence of a link between gut microbiota and primate social behavior. Overall, we find that enough empirical evidence already supports these predictions. Nonetheless, we conclude that studies with the necessary, sufficient, explicit, and available evidence are still scarce. Therefore, we reflect on the benefit of founding future analyses on the utility of social complexity as a theoretical framework.